Chronic Ulcer in Traumatic Lymphedema with Difficult Resolution: Treatment and Review - Godoy, José Maria Pereira de; Godoy, Livia Maria Pereira de; Godoy, Henrique José Pereira de (Brazilian Journal of Case Reports, 2025)
The aim of the present study was to report the resolution of a chronic ulcer in a patient with traumatic lymphedema by Godoy Method®. Male, 30 years old, reports that he suffered a car accident 12 years ago with trauma to the middle third of the right leg and skin necrosis where he underwent a graft and subsequent partial loss of the graft resulting in ulcer and lymphedema. He underwent treatment for a period of ten years, including 120 sessions in a hyperbaric chamber with no improvement. The patient underwent intensive treatment for lymphedema by Godoy Method® for 10 days. Stimulation of ulcer granulation was observed, with approximately 40% reduction in area and reduction in limb volume. He was discharged to continue treatment at home, wearing a grosgrain stocking and RAGodoy® device, which led to complete healing of the ulcer. Godoy Method® is effective for healing ulcer that are difficult to resolve.